Counter-Selection of Antimalarial Resistance Polymorphisms by Intermittent Preventive Treatment in Pregnancy. (2nd November 2019) - Huijben, Silvie; Macete, Eusebio; Mombo-Ngoma, Ghyslain; Ramharter, Michael; Kariuki, Simon; Desai, Meghna; Shi, Ya Ping; Mwangoka, Grace; Massougbodji, Achille; Cot, Michel; Ndam, Nicaise Tuikue; Uberegui, Estefania; et al.
Abstract: Background: Innovative approaches are needed to limit antimalarial resistance evolution. Understanding the role of intermittent preventive treatment in pregnancy (IPTp) on the selection for resistance and the impact such selection has on pregnancy outcomes can guide future interventions. Methods: Plasmodium falciparum isolates (n = 914) from 2 randomized clinical trials were screened for pfmdr1 copy number variation and pfcrt, pfmdr1, pfdhfr, and pfdhps resistance markers. The trials were conducted between 2010 and 2013 in Benin, Gabon, Kenya, and Mozambique to establish the efficacy of IPTp-mefloquine (MQ) compared with IPTp-sulphadoxine-pyrimethamine (SP) in human immunodeficiency virus (HIV)-uninfected and to IPTp-placebo in HIV-infected women. Results: In HIV-uninfected women, the prevalence of pfcrt mutants, pfdhfr/pfdhps quintuple mutants, and pfmdr1 copy number was similar between women receiving IPT-SP and IPTp-MQ. However, prevalence of pfmdr1 polymorphism 86Y was lower in the IPTp-MQ group than in the IPTp-SP group, and within the IPTp-MQ group it was lower at delivery compared with recruitment. No effect of IPTp-MQ on resistance markers was observed among HIV-infected women. The carriage of resistance markers was not associated with pregnancy outcomes. Conclusions: Selection of wild-type pfmdr1 polymorphism N86 by IPTp-MQ highlights the strong selective pressure IPTp can exert and the opportunity for using negative cross-resistance in drug choice for clinical treatment and IPTp. Abstract : Intermittent preventive antimalarial therapy of African pregnant women with mefloquine significantly reduced the prevalence of pfmdr N86Y mutants. This demonstrates the impact of interventions on the spread of resistance and how counter-selecting drugs could be exploited to curtail resistance evolution.